2021
DOI: 10.1016/j.jenvman.2020.111859
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and nitrite bacterial reduction at alkaline pH and high nitrate concentrations, comparison of acetate versus dihydrogen as electron donors

Abstract: Nitrate and nitrite bacterial reduction at alkaline pH and high nitrate concentrations, comparison of acetate versus dihydrogen as electron donors. (2021) Journal of Environmental Management, 280. 111859.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…In addition, it also provides a safety margin in case of unwanted alkalinization (Food Agriculture Organization of the United Nations, 2014 ). Although certain pH robustness is known for denitrifying microbiomes reporting microbial denitrification at up to pH 11–12 (Albina et al, 2021 ), this is, to our knowledge, not reported for bioelectrochemical denitrification. This broad pH range further supports the biotechnological potential of bioelectrochemical denitrification and extends its fields of application to moderate alkaline environments.…”
Section: Resultsmentioning
confidence: 59%
“…In addition, it also provides a safety margin in case of unwanted alkalinization (Food Agriculture Organization of the United Nations, 2014 ). Although certain pH robustness is known for denitrifying microbiomes reporting microbial denitrification at up to pH 11–12 (Albina et al, 2021 ), this is, to our knowledge, not reported for bioelectrochemical denitrification. This broad pH range further supports the biotechnological potential of bioelectrochemical denitrification and extends its fields of application to moderate alkaline environments.…”
Section: Resultsmentioning
confidence: 59%
“…IET Associated Syntrophic Coupling between Syntrophomonas and Denitrified Denitrifiers of Rhodoclyclaceae. Despite such coupling of acetate oxidation and denitrification observed in several digestion reactors, 81,82 this study provided the first convincing evidence for such coupling in a TAD system and revealed its association with conductive material-mediated interspecies electron transfer (MIET). Therefore, IET capabilities of Rhodoclyclaceae species and the ecological implication of its coupling with syntrophic acetate oxidation in AD systems deserve further investigations.…”
Section: Spatial Association Co-occurrence Network Based On Micron-sc...mentioning
confidence: 81%
“…Studies have shown that maintaining adequate alkalinity concentrations is essential to maintain nitrification [ 19 ], and at pH near neutral and alkaline variations in the range of 6.5–9.0, nitrite nitrogen accumulation rises gradually with increasing pH, with pH = 9.0 being more favorable for the accumulation of nitrite nitrogen in denitrification [ 20 ]. In the presence of NO, pH has a strong influence on the kinetics and mechanism of abiotic transformation, and low pH conditions tend to easily break S-N and N-C bonds and promote nitrification and nitrosation reactions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%